Pregnancy Rate and Sex-ratio of Calves Born to Sex-sorted Semen in Murrah Buffaloes - Ingawale, Maheshkumar Vitthalarao; Sawant, Sujata Sudamrao; Dhatonde, Akshay Shripati; Deshmukh, Shyam Ganesh; Pawshe, Chaitanya Hemendrakumar (The Indian Journal of Animal Reproduction, 2022)
The research was carried out to study the pregnancy rate and sex-ratio of female calves born through sex-sorted semen in buffaloes. Murrah and graded Murrah buffaloes were inseminated with sex-sorted semen (n=44) and with conventional semen (n=20). Out of which 17 (38.63%) and 9 (45%) buffaloes were found pregnant in sex-sorted and conventional semen groups, respectively. Out of seventeen calves born with inseminations of sex-sorted semen, 15 (88.23%) were female calves while two (11.77%) calf born were male. Out of nine calves born with inseminations of conventional semen, 5 (55.55%) were females and four (44.45%) were male. Female calves born were 32.68 % more in sex-sorted semen compared to conventional semen in buffaloes so female sex-sorted semen should be utilized for production of more number of female calves in buffaloes.